Production of minimally disturbed synchronous cultures of hematopoietic cells - Thornton, Maureen (BioTechniques, 2002)
A method is describedforproducing sizable quantities of synchronously dividing, minimally disturbed mammalian cells. Cultures were grown immobilized on surfaces such that cell division within the population resulted in the continuous release of synchronous newborn cells. As judged by the quality and duration of synchronous growth, cell size distributions, and DNA compositions, newborn mouse L1210 cells grew with a very high level of synchrony without overt evidence of growth disturbances. The technology should be applicable to a variety of hematopoietic cells, as evidenced by similar results with human MOLT-4 and U937 cell lines